“We are not stray leaves blowing about in the wind”: exploring the impact of Family Wellbeing empowerment research, 1998–2021 - Perera, Niru; Tsey, Komla; Heyeres, Marion; Whiteside, Mary; Baird, Leslie; McCalman, Janya; Cadet-James, Yvonne; Calabria, Bianca; Hamilton, Michael; Li, Yan; Zuchowski, Ines; Sims, Kearrin; et al. (BioMed Central, 2022)
Background: An Aboriginal-developed empowerment and social and emotional wellbeing program, known as Family Wellbeing (FWB), has been found to strengthen the protective factors that help Indigenous Australians to deal with the legacy of colonisation and intergenerational trauma. This article reviews the research that has accompanied the implementation of the program, over a 23 year period. The aim is to assess the long-term impact of FWB research and identify the key enablers of research impact and the limitations of the impact assessment exercise. This will inform more comprehensive monitoring of research impact into the future.